2019
DOI: 10.1083/jcb.201811147
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated GTP-binding protein 1 modulates ciliogenesis via an interaction with Dishevelled

Abstract: Cilia are critical for proper embryonic development and maintaining homeostasis. Although extensively studied, there are still significant gaps regarding the proteins involved in regulating ciliogenesis. Using the Xenopus laevis embryo, we show that Dishevelled (Dvl), a key Wnt signaling scaffold that is critical to proper ciliogenesis, interacts with Drg1 (developmentally regulated GTP-binding protein 1). The loss of Drg1 or disruption of the interaction with Dvl reduces the length and number of cilia and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Prior work demonstrated that within multicilliated cells of the Xenopus skin Daam1, a component of the planar cell polarity pathway, is important for the proper development of motile cilia [26,39]. Additionally, the cilia have been found to be important for cell polarity and cell divisions [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…Prior work demonstrated that within multicilliated cells of the Xenopus skin Daam1, a component of the planar cell polarity pathway, is important for the proper development of motile cilia [26,39]. Additionally, the cilia have been found to be important for cell polarity and cell divisions [9,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is a highly conserved gene that is expressed in almost all tissues. DRG1 plays an important role during embryonic development [3][4][5]. Although DRG1 is down-regulated after birth, high expression of DRG1 is observed in rapidly growing tissues and organs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DRG1 has also been implicated in the regulation of cilia [ 80 ]. Cilia are long, thin, microtubule structures that protrude from the surface of cells where they are important for signalling pathways and development [ 81 ].…”
Section: Structure Biochemistry and Regulation Of Drgsmentioning
confidence: 99%
“…Cilia are long, thin, microtubule structures that protrude from the surface of cells where they are important for signalling pathways and development [ 81 ]. Lee et al suggested that DRG1 promotes the formation of cilia independently of its GTPase activity, through an interaction with the Wnt signalling activator Dishevelled (Dvl) [ 80 ]. DRG1 and Dvl interact with the protein Daam1 (Dishevelled-associated activator of morphogenesis 1), which in turn promotes the formation of the apical actin network that is required for proper basal body localization and cilia formation [ 80 ].…”
Section: Structure Biochemistry and Regulation Of Drgsmentioning
confidence: 99%